Predictors of Student Participation in The Kampus Merdeka Program: Testing The Extended Theory of Planned Behaviour with Incentives Variable - Amalin, Najin Khoirul; Putro, Utomo Sarjono (Universitas Muhammadiyah Surakarta, 2023)
The Kampus Merdeka program aims to scrape the gap between education and the rapidly changing work environment that has become an issue nowadays. Three years after launching the program, no research has examined the predictors of student participation in the program that are important for the policy maker to re-evaluate the program. On the other hand, the government spends a lot of money to run the program and give direct benefit for the students who participated in the program, but still not create enough opportunity for all students. This study analyzes the predictors and the impact of government incentives on students' willingness to participate. Using theory of planned behavior with additional incentive variables, the researcher distributes the survey through an online questionnaire to the students who are eligible to participate in Kampus Merdeka. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to analyze the significance predictors. As a result, attitude, subjective norm, and incentives significantly influenced students' intention to participate in the program. Intention, in turn, positively influenced actual participation. In contrast, Perceived behavioral control did not significantly affect intention or behavior. Attitude, subjective norm, and incentives play vital roles in encouraging student participation in the Kampus Merdeka program. These findings can guide policymakers and institutions in enhancing program effectiveness.